Composição tecidual e avaliação da carne de cordeiros Lacaune X Texel - Arnoni, Raquel Klumb (2010)
Effect of sex on tissue composition was evaluated, as well as instrumental and subjective evaluation of meat from cross-bred Lacaune X Texel lambs grown in improved native pasture and supplemented with ration and hay. Twenty two lambs (11 females and 11 males), were used born in September 2007 and slaughtered in January 2008.Slaughtering criterion for lambs was based on body condition (ranking from 2.5 to 3.5). After slaughter the carcasses were placed in cold room with forced air and temperature within ± 1°C. Subjective evaluations of texture, marbling and color of meat were performed. Other instrumental objective measures were made, such as the ability to retain water, as measured by the method of loss by pressure, and the color, evaluated by two methods: physicochemical and using a colorimeter obtained through the system CIELAB. The pH and temperature of the Longissimus dorsi muscle were measured at 0 hours, 24 hours and 48 hours post-mortem. For the analysis of tissue composition the separation of the following tissues was performed: subcutaneous fat, intermuscular fat, other, muscle and bone. The experimental design was completely randomized, with two treatments and eleven replications. The data were subjected to analysis of variance. Males and females from crossbreeding Lacaune X Texel present the same meat quality for subjective and instrumental characteristics.